Steel plate and its manufacturing method

The steel sheet with a high volume fraction of tempered martensite and specific residual austenite carbon concentration achieves superior yield and tensile strengths, along with enhanced delayed fracture resistance, addressing the limitations of existing high-strength steel sheets for automotive applications.

JP7657372B2Active Publication Date: 2025-04-04JFE STEEL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024532657
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-24
Filing Date
2022-04-20
Publication Date
2025-04-04
Estimated Expiration
2042-04-20

AI Technical Summary

Technical Problem

Existing high-strength steel sheets for automotive applications lack sufficient yield strength, tensile strength, and delayed fracture resistance, particularly in correlation with impact absorption and phosphate treatment properties.

Method used

A steel sheet composition with 90% or more tempered martensite, 1-7% residual austenite, and 3-9% bainitic ferrite and fresh martensite, along with specific carbon concentration in residual austenite, achieving tensile strength of 1470-1650 MPa and yield strength of 1100 MPa or more.

Benefits of technology

The steel sheet exhibits high yield strength, high tensile strength, and excellent delayed fracture resistance, making it suitable for automotive structural components that require enhanced collision resistance and weight reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657372000001
    Figure 0007657372000001
  • Figure 0007657372000002
    Figure 0007657372000002
  • Figure 0007657372000003
    Figure 0007657372000003
Patent Text Reader

Abstract

The steel sheet of the present invention has a composition containing predetermined amounts of C, Si, Mn, Cu, P, S, Al, and N, and optionally further containing predetermined amounts of one or more elements selected from the group consisting of Ti, B, Nb, Cr, V, Mo, Ni, As, Sb, Sn, Ta, Ca, Mg, Zn, Co, Zr, and REM, with the balance being Fe and unavoidable impurities, and a structure containing, by volume, 90% or more tempered martensite, 1 to 7% retained austenite, 3 to 9% in total of one or both of bainitic ferrite and fresh martensite, and 0 to 5% ferrite, wherein the carbon concentration in the retained austenite is 0.35% or more, and a tensile strength TS of 1470 to 1650 MPa, and a yield strength YS of 1100 MPa or more.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to U.S. Provisional Application No. 63 / 236,426, entitled "Steel Sheet and Method of Producing Same," filed August 24, 2021, the entire disclosure of which is incorporated herein by reference. [Technical field]

[0002] The present invention relates to a steel sheet and a method for producing the same. [Background technology]

[0003] In order to reduce the weight of vehicles and simultaneously reduce CO2 emissions and improve crashworthiness, the strength of steel sheets for automobiles is being increased, and new regulations are being introduced one after another. As a result, the number of cases in which high-strength steel sheets with a tensile strength (TS) of 1470 MPa or more are being used in the main structural parts that make up automobiles is increasing.

[0004] High-strength steel sheets used in automobiles are required to have excellent yield strength (YS) and tensile strength (TS). For example, automobile frame parts such as bumpers are required to have excellent shock absorption properties during a collision, so it is preferable to use steel sheets with excellent yield strength (YS) and tensile strength (TS), which are correlated with shock absorption properties.

[0005] In addition, automotive steel sheets are painted before use, and are subjected to chemical conversion treatment such as phosphating as a pretreatment for painting. Since delayed fracture due to hydrogen infiltrated from chemicals during the chemical conversion treatment of steel sheets is a concern, automotive steel sheets are required to have excellent delayed fracture resistance. In order to increase the application rate of high-strength steel sheets to automotive parts, it is required that these properties are comprehensively satisfied.

[0006] In response to these requirements, various high-strength steel sheets have been proposed. For example, Patent Document 1 describes a steel sheet having a composition, in mass%, of C: 0.10% to 0.6%, Si: 1.0% to 3.0%, Mn: over 2.5% to 10.0%, P: 0.05% or less, S: 0.02% or less, Al: 0.01% to 1.5%, N: 0.005% or less, Cu: 0.05% to 0.50% or less, with the balance being iron and unavoidable impurities, the surface coverage of the steel sheet by oxides mainly composed of Si is 1% or less, the surface coverage of the steel sheet by iron-based oxides is 40% or less, and Cu is 0.05% or less. S / Cu B is 4.0 or less (Cu S is the Cu concentration in the steel sheet surface layer, Cu B is the Cu concentration in the base material) and has a tensile strength of 1180 MPa or more (Claim 1)." In this steel sheet, "the steel structure is tempered martensite and / or bainite at a total volume fraction of 40% to 100%, ferrite at a volume fraction of 0% to 60%, and retained austenite at a volume fraction of 2% to 30% (Claim 2)."

[0007] Patent Document 2 also describes a composition containing, by mass%, C: 0.06-0.25%, Si: 0.6-2.5%, Mn: 2.3-3.5%, P: 0.02% or less, S: 0.01% or less, sol.Al: less than 0.50%, N: less than 0.015%, with the balance being iron and unavoidable impurities, and a composition containing, by area ratio, ferrite: 6-80%, a structure consisting of one or more of upper bainite, fresh martensite, tempered martensite, lower bainite, and retained γ: 20-94%, by volume ratio, retained γ: 7-20%, a grain width of 0.18-0.60 μm, a grain length of 1.7-7.0 μm, and an aspect ratio of 5-15. UB Area ratio of: S γUB is 0.2 to 5%, and the total area ratio of fresh martensite having a circle equivalent particle diameter of 1.5 to 15 μm and an aspect ratio of 3 or less and / or residual γ particles having a circle equivalent particle diameter of 1.5 to 15 μm and an aspect ratio of 3 or less: S γBlock The steel sheet has a Cr content of 3% or less (including 0%) (Claim 1)." [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2017 / 141953 (US2019 / 040490A1) [Patent Document 2] International Publication No. 2018 / 190416 (US2020 / 157647A1) Summary of the Invention [Problem to be solved by the invention]

[0009] The purpose of Patent Document 1 is to provide a high-strength steel sheet having a tensile strength of 1180 MPa or more and excellent delayed fracture resistance and phosphate treatability. However, the description in Patent Document 1 does not take into consideration the yield strength (YS) that correlates with the impact absorption during a collision. In addition, the evaluation of delayed fracture resistance is performed using test pieces that have been ground, and the change in delayed fracture resistance due to shear conditions is not taken into consideration.

[0010] The purpose of Patent Document 2 is to provide a steel sheet having a tensile strength of 780 to 1470 MPa and having high ductility and excellent stretch flange formability. However, Patent Document 2 does not take into consideration the yield strength (YS) and delayed fracture resistance properties that are correlated with impact absorption during a collision.

[0011] In view of the above problems, the present invention has an object to provide a steel sheet having high yield strength YS, high tensile strength TS, and excellent delayed fracture resistance, and a manufacturing method thereof. [Means for solving the problem]

[0012] Means for Solving the Problems The present inventors have conducted extensive research in order to solve the above problems and have discovered the following.

[0013] (1) By setting the amount of tempered martensite to 90% or more, a TS of 1470 MPa or more can be achieved.

[0014] (2) By setting the amount of tempered martensite to 90% or more and the carbon concentration in the retained austenite to 0.35% or more, a YS of 1100 MPa or more can be achieved.

[0015] (3) By controlling the amount of retained austenite to 7% or less and the total amount of bainitic ferrite and fresh martensite to 9% or less, excellent resistance to delayed fracture can be achieved.

[0016] The gist and configuration of the present invention, which has been completed based on the above findings, are as follows.

[0017] [1] In mass percent, C: 0.24-0.28%, Si: 0.40 to 0.80%, Mn: 2.30-2.70%, Cu: 0.010~1.000%, P: 0.001~0.100%, S: 0.0001~0.0200%, Al: 0.010 to 0.050%, and N: 0.0010~0.0100% Contains Optionally, Ti: 0.1000% or less, B: 0.01000% or less, Nb: 0.1000% or less, Cr: 1.00% or less, V: 0.100% or less, Mo: 0.500% or less, Ni: 0.500% or less, As: 0.500% or less, Sb: 0.200% or less, Sn: 0.200% or less, Ta: 0.100% or less, Ca: 0.0200% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co: 0.0200% or less, Zr: 0.0200% or less, and REM: 0.0200% or less and a component composition further comprising one or more selected from the group consisting of: In terms of volume ratio, Tempered martensite: 90% or more, Retained austenite: 1-7%, Bainitic ferrite and / or fresh martensite: 3-9% in total, and Ferrite: 0 to 5% a structure in which the carbon concentration in the retained austenite is 0.35% or more; Tensile strength TS of 1470 to 1650 MPa; Yield strength YS of 1100 MPa or more, A steel plate having

[0018] [2] The steel plate according to the above [1], wherein the yield strength YS is 1200 MPa or more.

[0019] [3] Prepare an unplated steel sheet having the composition described in [1] above, The steel plate is heated to a heating temperature T1 of 850° C. or higher, The steel sheet is held at the heating temperature T1 for 10 to 1000 seconds, The steel sheet is cooled from the heating temperature T1 to a cooling stop temperature T2 of 130 to 170 ° C. (i) an average cooling rate from the heating temperature T1 to 550°C: 16°C / s or more; and (ii) Average cooling rate from 550°C to the cooling stop temperature T2: 150°C / s or less Continuously cool under the conditions of The steel sheet is held at the cooling stop temperature T2 for 1 to 200 seconds, The steel plate is heated from the cooling stop temperature T2 to a tempering temperature T3 of 280 to 350 ° C. at an average heating rate of 10 ° C. / s or more, The steel sheet is held at the tempering temperature T3 for 10 to 1000 seconds, The steel plate is cooled to 50°C or less. A method for producing a steel plate, comprising the steps of: producing the steel plate according to the above item [1].

[0020] [4] A method for producing a steel sheet according to the above [3], comprising the step of subjecting the steel sheet to temper rolling at an elongation rate of 0.1 to 1.0% after the cooling to 50°C or less. Effect of the Invention

[0021] The steel plate of the present invention has high yield strength YS, high tensile strength TS, and excellent resistance to delayed fracture. According to the method for producing a steel plate of the present invention, a steel plate having high yield strength YS, high tensile strength TS, and excellent resistance to delayed fracture can be produced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] A steel plate (high strength steel plate) according to one embodiment of the present invention has a predetermined component composition, a predetermined structure, and predetermined mechanical properties.

[0023] First, the chemical composition of the steel sheet according to this embodiment will be described. In the following description, "%" representing the content of each component element in the steel sheet means "mass %" unless otherwise specified.

[0024] C: 0.24% or more and 0.28% or less C is one of the important basic components of steel, and in the present invention, it is an important element that affects the carbon concentration and TS in the retained austenite. If the C content is less than 0.24%, (i) the carbon concentration in the retained austenite decreases, causing a decrease in YS, and (ii) it becomes difficult to achieve a TS of 1470 MPa or more. Therefore, the C content is set to 0.24% or more, and preferably 0.25% or more. On the other hand, if the C content exceeds 0.28%, the strength of the steel sheet increases too much, making it difficult to achieve a TS of 1650 MPa or less. Therefore, the C content is set to 0.28% or less, and preferably 0.27% or less.

[0025] Si: 0.40% or more and 0.80% or less Si is one of the important basic components of steel, and in the present invention, it is an important element that affects the amount of retained austenite and the carbon concentration in the retained austenite. If the Si content is less than 0.40%, the carbon concentration in the retained austenite decreases, and the YS decreases. Therefore, the Si content is set to 0.40% or more, and preferably 0.50% or more. On the other hand, if the Si content exceeds 0.80%, the phase fraction of the retained austenite increases, and the delayed fracture resistance property decreases. It is also known that the phosphating property decreases with an increase in the Si content. Therefore, the Si content is set to 0.80% or less, and preferably 0.70% or less.

[0026] Mn: 2.30% or more and 2.70% or less Mn is one of the important basic components of steel, and in the present invention, it is an important element that affects the phase fraction of tempered martensite, the phase fraction of ferrite, and delayed fracture resistance. If the Mn content is less than 2.30%, the phase fraction of ferrite increases, making it difficult to achieve a TS of 1470 MPa or more. Therefore, the Mn content is set to 2.30% or more, preferably 2.40% or more. On the other hand, if the Mn content exceeds 2.70%, the delayed fracture resistance decreases. It is also known that the phosphating property decreases with an increase in the Mn content. Therefore, the Mn content is set to 2.70% or less, preferably 2.60% or less.

[0027] Cu: 0.010% or more and 1.000% or less Cu is one of the important basic components of steel, and in the present invention, it is an important element that affects delayed fracture resistance. If the Cu content is less than 0.010%, the delayed fracture resistance is reduced. Therefore, the Cu content is set to 0.010% or more, and preferably 0.050% or more. On the other hand, if the Cu content exceeds 1.000%, the slab becomes embrittled and easily cracked in the casting process, and productivity is significantly reduced. It is also known that the phosphating property decreases with an increase in the Cu content. Therefore, the Cu content is set to 1.000% or less, and preferably 0.900% or less.

[0028] P: 0.001% or more and 0.100% or less If the P content exceeds 0.100%, P segregates at the prior austenite grain boundaries, embrittling the grain boundaries and reducing the delayed fracture resistance. Therefore, the P content is set to 0.100% or less, preferably 0.070% or less, and more preferably 0.050% or less. In addition, due to restrictions on production technology, the P content is typically set to 0.001% or more.

[0029] S: 0.0001% or more and 0.0200% or less If the S content exceeds 0.0200%, S exists as sulfides and may become the starting point of delayed fracture. Therefore, the S content is set to 0.0200% or less, preferably 0.0100% or less, and more preferably 0.0050% or less. In addition, due to restrictions on production technology, the S content is typically set to 0.0001% or more.

[0030] Al: 0.010% or more and 0.050% or less Al increases the strength of the steel sheet and makes it easier to achieve a TS of 1470 MPa or more. Therefore, the Al content is set to 0.010% or more. However, if the Al content exceeds 0.050%, the amount of ferrite increases, making it difficult to achieve a TS of 1470 MPa or more. Therefore, the Al content is set to 0.050% or less, preferably 0.040% or less, and more preferably 0.020% or less.

[0031] N: 0.0010% or more and 0.0100% or less If the N content exceeds 0.0100%, the slab becomes brittle and easily cracks during the casting process, significantly reducing productivity. Therefore, the N content is set to 0.0100% or less, preferably 0.0070% or less, and more preferably 0.0050% or less. In addition, due to restrictions on production technology, the N content is set to 0.0010% or more.

[0032] In various embodiments, the chemical composition of the steel sheet contains one or more elements selected from Ti, B, and Nb in the following content ranges.

[0033] Ti:0.1000% or less Ti increases the strength of the steel plate and makes it easier to achieve a TS of 1470 MPa or more. Therefore, the Ti content is preferably 0.0010% or more, and more preferably 0.0050% or more. On the other hand, if the Ti content exceeds 0.1000%, the slab becomes embrittled and easily cracked during the casting process, and productivity drops significantly. Therefore, when Ti is added, the Ti content is 0.1000% or less, and preferably 0.0600% or less.

[0034] B: 0.01000% or less B suppresses the formation of ferrite during cooling, making it easier to achieve a TS of 1470 MPa or more. Therefore, the B content is preferably 0.00010% or more, and more preferably 0.00100% or more. On the other hand, if the B content exceeds 0.01000%, the slab becomes embrittled and easily cracked during the casting process, significantly reducing productivity. Therefore, when B is added, the B content is 0.01000% or less, and preferably 0.00500% or less.

[0035] Nb: 0.1000% or less Nb increases the strength of the steel plate, facilitates the realization of a TS of 1470 MPa or more, and improves delayed fracture resistance by combining with C to form Nb-based carbides, which act as hydrogen trapping sites. Therefore, the Nb content is preferably 0.0010% or more, and more preferably 0.0050% or more. On the other hand, if the Nb content exceeds 0.1000%, the slab becomes embrittled and prone to cracking during the casting process, significantly reducing productivity. Therefore, when Nb is added, the Nb content is 0.1000% or less, and preferably 0.0600% or less.

[0036] [Cu] + 10 × [Nb]: 0.15 or more and 2.00 or less (optimal condition) As a result of the research by the present inventors, it was found that when [Cu] + 10 × [Nb] is 0.15 or more, the delayed fracture resistance property is improved. Therefore, it is preferable that [Cu] + 10 × [Nb] is 0.15 or more. Here, [Cu] and [Nb] respectively mean the amount of Cu and the amount of Nb (mass%) in the composition. On the other hand, it is preferable that [Cu] + 10 × [Nb] is 2.00 or less, from the upper limit of the amount of Cu and the amount of Nb (mass%).

[0037] In various embodiments, the composition of the steel sheet includes one or more selected from Cr, V, Mo, Ni, As, Sb, Sn, Ta, Ca, Mg, Zn, Co, Zr, and REM in the following content ranges.

[0038] Cr:1.00% or less Cr not only plays a role as a solid solution strengthening element, but also stabilizes austenite during the cooling process during continuous annealing and suppresses the formation of ferrite, thereby increasing the strength of the steel sheet. To obtain these effects, the Cr content is preferably 0.01% or more, and more preferably 0.02% or more. On the other hand, if the Cr content exceeds 1.00%, a large amount of coarse precipitates and inclusions are formed, reducing the ultimate deformability of the steel. Therefore, when Cr is added, the Cr content is set to 1.00% or less, and preferably 0.70% or less.

[0039] V:0.100% or less V increases the strength of steel sheet. To obtain this effect, the V content is preferably 0.001% or more, and more preferably 0.005% or more. On the other hand, if the V content exceeds 0.100%, a large amount of coarse precipitates and inclusions are generated, lowering the ultimate deformability of the steel. Therefore, when V is added, the V content is set to 0.100% or less, and preferably 0.060% or less.

[0040] Mo: 0.500% or less Mo not only plays a role as a solid solution strengthening element, but also stabilizes austenite during the cooling process during continuous annealing and suppresses the formation of ferrite, thereby increasing the strength of the steel sheet. To obtain these effects, the Mo content is preferably 0.010% or more, and more preferably 0.020% or more. On the other hand, if the Mo content exceeds 0.500%, a large amount of coarse precipitates and inclusions are formed, which reduces the ultimate deformability of the steel. Therefore, when Mo is added, the Mo content is 0.500% or less, and preferably 0.450% or less.

[0041] Ni: 0.500% or less Ni stabilizes austenite during the cooling process during continuous annealing and suppresses the formation of ferrite, thereby increasing the strength of the steel sheet. To obtain these effects, the Ni content is preferably 0.010% or more, more preferably 0.020% or more. On the other hand, if the Ni content exceeds 0.500%, the slab becomes embrittled and easily cracked during the casting process, and productivity is significantly reduced. Therefore, when Ni is added, the Ni content is 0.500% or less, preferably 0.450% or less.

[0042] As: 0.500% or less As increases the strength of steel sheet. To obtain this effect, the As content is preferably 0.001% or more, and more preferably 0.005% or more. On the other hand, if the As content exceeds 0.500%, a large amount of coarse precipitates and inclusions are generated, lowering the ultimate deformability of the steel. Therefore, when As is added, the As content is set to 0.500% or less, and preferably 0.060% or less.

[0043] Sb: 0.200% or less Sb suppresses surface softening and increases the strength of the steel sheet. To obtain this effect, the Sb content is preferably 0.001% or more, and more preferably 0.005% or more. On the other hand, if the Sb content exceeds 0.200%, the slab becomes embrittled and easily cracked during the casting process, and productivity drops significantly. Therefore, when Sb is added, the Sb content is set to 0.200% or less, and preferably 0.100% or less.

[0044] Sn: 0.200% or less Sn suppresses surface softening and increases the strength of the steel sheet. To obtain this effect, the Sn content is preferably 0.001% or more, and more preferably 0.005% or more. On the other hand, if the Sn content exceeds 0.200%, the slab becomes brittle and easily cracks during the casting process, and productivity drops significantly. Therefore, when Sn is added, the Sn content is set to 0.200% or less, and preferably 0.100% or less.

[0045] Ta:0.100% or less Ta increases the strength of steel sheet. To obtain this effect, the Ta content is preferably 0.001% or more, and more preferably 0.005% or more. On the other hand, if the Ta content exceeds 0.100%, a large amount of coarse precipitates and inclusions are generated, lowering the ultimate deformability of the steel. Therefore, when Ta is added, the Ta content is 0.100% or less, and preferably 0.050% or less.

[0046] Ca:0.0200% or less Ca is an element used for deoxidization, and is also an element that is effective in making sulfides spheroidal, improving the ultimate deformability of steel sheets, and improving delayed fracture resistance. To achieve these effects, the Ca content is preferably 0.0001% or more. On the other hand, if the Ca content exceeds 0.0200%, a large amount of coarse precipitates and inclusions are generated, reducing the ultimate deformability of the steel. Therefore, when Ca is added, the Ca content is set to 0.0200% or less.

[0047] Mg: 0.0200% or less Mg is an element used for deoxidization, and is also an effective element for making sulfides spheroidal, improving the ultimate deformability of steel sheets, and improving delayed fracture resistance. To achieve these effects, the Mg content is preferably 0.0001% or more. On the other hand, if the Mg content exceeds 0.0200%, a large amount of coarse precipitates and inclusions are generated, lowering the ultimate deformability of the steel. Therefore, when Mg is added, the Mg content is set to 0.0200% or less.

[0048] Zn: 0.0200% or less Zn is an element that is effective in making the shape of inclusions spheroidal, improving the ultimate deformability of the steel sheet, and improving delayed fracture resistance. To obtain these effects, the Zn content is preferably 0.0010% or more. On the other hand, if the Zn content exceeds 0.0200%, a large amount of coarse precipitates and inclusions are generated, lowering the ultimate deformability of the steel. Therefore, when Zn is added, the Zn content is set to 0.0200% or less.

[0049] Co:0.0200% or less Co is an element that is effective in making the shape of inclusions spheroidal, improving the ultimate deformability of the steel sheet, and improving delayed fracture resistance. To achieve this effect, the Co content is preferably 0.0010% or more. On the other hand, if the Co content exceeds 0.0200%, a large amount of coarse precipitates and inclusions are generated, lowering the ultimate deformability of the steel. Therefore, when Co is added, the Co content is set to 0.0200% or less.

[0050] Zr: 0.0200% or less Zr is an element that is effective in making the shape of inclusions spheroidal, improving the ultimate deformability of the steel sheet, and improving delayed fracture resistance. To obtain these effects, the Zr content is preferably 0.0010% or more. On the other hand, if the Zr content exceeds 0.0200%, a large amount of coarse precipitates and inclusions are generated, lowering the ultimate deformability of the steel. Therefore, when Zr is added, the Zr content is set to 0.0200% or less.

[0051] REM: 0.0200% or less REM (Rare Earth Metal) is an element that is effective in making the shape of inclusions spherical, improving the ultimate deformability of steel plate, and improving delayed fracture resistance. To achieve this effect, the REM content is preferably 0.0010% or more. On the other hand, if the REM content exceeds 0.0200%, a large amount of coarse precipitates and inclusions are generated, reducing the ultimate deformability of the steel. Therefore, when REM is added, the REM content is set to 0.0200% or less.

[0052] In the composition of the steel sheet, the balance other than the above elements is composed of Fe and inevitable impurities. Note that, when the content of the above optional elements is less than the preferable lower limit value, the above optional elements are included as inevitable impurities so as not to impair the effects of the present invention.

[0053] Next, the steel structure of the steel plate according to this embodiment will be described. The steel structure includes tempered martensite as a main phase, a predetermined amount of retained austenite, a predetermined amount of one or both of bainitic ferrite and fresh martensite, and optional ferrite.

[0054] Tempered martensite: Volume fraction 90% or more Having tempered martensite as the main phase is useful for achieving a TS of 1470 MPa or more. From the viewpoint of increasing the TS, the amount of tempered martensite needs to be 90% or more, preferably 92% or more, and more preferably 94% or more.

[0055] Here, the method for measuring the volume fraction of tempered martensite is as follows. After polishing the L-section of the steel plate, it is corroded with 3 volume % nital. The L-section is observed at 1 / 4 of the plate thickness (a position corresponding to 1 / 4 of the plate thickness in the depth direction from the steel plate surface) at 10 fields of view at a magnification of 2000 times using an SEM to obtain a structural image. In the above structural image, the tempered martensite has a structure with fine internal irregularities and carbides inside. The area fraction of the tempered martensite is obtained in the 10 fields of view, and the average value is calculated. Since the area fraction of the tempered martensite is almost constant in the direction perpendicular to the L-section, this average value is regarded as the "volume fraction of tempered martensite".

[0056] Retained austenite: Volume fraction: 1% to 7% If the amount of retained austenite exceeds 7%, the delayed fracture resistance property is reduced. The reason for the reduction in delayed fracture resistance property due to retained austenite is that the retained austenite is transformed into processing-induced martensite by processing, and becomes a structure that is harder than the tempered martensite, which is the main phase. Therefore, the amount of retained austenite is set to 7% or less, and preferably to 6% or less. On the other hand, the amount of retained austenite depends on the cooling stop temperature T2, and it is difficult to set the cooling stop temperature T2 to less than 130°C due to production technology constraints. Therefore, the amount of retained austenite is set to 1% or more, and preferably to 2% or more.

[0057] Here, the method for measuring the volume fraction of retained austenite is as follows. The steel sheet is polished from the surface to expose the surface at 1 / 4 of the sheet thickness. In the first step of this polishing, mechanical polishing is performed from the surface of the steel sheet to a surface that is 0.1 mm closer to the surface than the 1 / 4 position of the sheet thickness. Then, in the second step, chemical polishing is performed to reduce the thickness of the steel sheet by 0.1 mm to expose the surface at the 1 / 4 position of the sheet thickness. For the exposed surface at the 1 / 4 position of the sheet thickness, the integrated intensity of the diffraction peaks of the {200}, {220}, and {311} planes of fcc iron and the {200}, {211}, and {220} planes of bcc iron is measured using CoKα radiation in an X-ray diffractometer. The integrated intensity ratio (fcc / (fcc+bcc)) is calculated for all combinations (9 in total) of the three faces of fcc iron and the three faces of bcc iron. The average value of the nine integrated intensity ratios obtained is calculated and used as the "volume fraction of retained austenite".

[0058] Bainitic ferrite and / or fresh martensite: Total volume fraction: 3% to 9% If the total amount of bainitic ferrite and fresh martensite exceeds 9%, the delayed fracture resistance property is reduced. The reason for the reduction in delayed fracture resistance due to bainitic ferrite and fresh martensite is that both of them have structures with different hardness from the main phase, tempered martensite. Therefore, the total amount is set to 9% or less, preferably 8% or less, and more preferably 5% or less. On the other hand, due to constraints on production technology, the total amount is set to 3% or more.

[0059] Here, the method for measuring the total volume ratio of bainitic ferrite and fresh martensite is as follows. After polishing the L-section of the steel plate, it is etched with 3 volume % nital. The L-section is observed at 1 / 4 of the plate thickness (a position corresponding to 1 / 4 of the plate thickness in the depth direction from the steel plate surface) at 10 fields of view at a magnification of 2000 times using an SEM to obtain a structural image. In the above structural image, bainitic ferrite, fresh martensite, and retained austenite have fine internal irregularities and are structures that do not have carbides inside. The total area ratios of these three phases are obtained in the 10 fields of view, and the average value is calculated. Since the total area ratios of these three phases are almost constant in the direction perpendicular to the L-section, this average value is regarded as the "total volume ratio" of these three phases. The total volume ratio of bainitic ferrite and fresh martensite can be obtained by subtracting the volume ratio of retained austenite measured by the above-mentioned method from the total volume ratio of these three phases.

[0060] Ferrite: Volume percentage: 0% to 5% Since ferrite is a soft structure, if the ferrite content exceeds 5%, it becomes difficult to achieve a TS of 1470 MPa or more. Therefore, the ferrite content is set to 5% or less, preferably 3% or less, and more preferably 2% or less.

[0061] The method for measuring the volume fraction of ferrite is as follows. After polishing the L-section of the steel plate, it is corroded with 3 volume % nital. The L-section is observed at 1 / 4 of the plate thickness (a position corresponding to 1 / 4 of the plate thickness in the depth direction from the steel plate surface) in 10 fields of view at a magnification of 2000 times using an SEM to obtain a structural image. In the above structural image, the ferrite is a structure with a concave portion and a flat interior. The area fraction of ferrite is obtained in the 10 fields of view, and the average value is calculated. Since the area fraction of ferrite is almost constant in the direction perpendicular to the L-section, this average value is regarded as the "volume fraction of ferrite."

[0062] Carbon concentration in retained austenite: 0.35% or more If the carbon concentration in the retained austenite is less than 0.35%, the main cause of yielding of the steel sheet changes from tempered martensite to the retained austenite, making it difficult to achieve a YS of 1100 MPa or more. Therefore, the carbon concentration in the retained austenite is set to 0.35% or more, and preferably 0.40% or more. On the other hand, due to constraints in production technology, the carbon concentration in the retained austenite is preferably set to 1.00% or less.

[0063] The method for measuring the carbon concentration in the retained austenite using CoKα radiation with an X-ray diffractometer is as follows: First, the lattice constant a of the retained austenite was calculated from the diffraction peak shift amount of the (220) plane of the austenite using formula (1), and the carbon concentration in the retained austenite was calculated by substituting the obtained lattice constant a of the retained austenite into formula (2). a = 1.79021√2 / sinθ (1) a=3.578+0.00095[Mn]+0.022[N]+0.0006[Cr]+0.0031[Mo]+0.0051[Nb]+0.0039[Ti]+0.0056[Al]+0.033[C]...(2) In addition, a: Lattice constant of retained austenite (Å) θ: (220) diffraction peak angle divided by 2 (rad) [M]: Content of element M in retained austenite (mass%) That is, [C] in formula (2) is the carbon concentration in the retained austenite. However, in the present disclosure, the content (mass%) of element M other than C in the retained austenite is the content (mass%) in the entire steel.

[0064] Tensile strength TS: 1470MPa or more, 1650MPa or less The steel plate of this embodiment has a tensile strength TS of 1470 MPa or more and 1650 MPa or less.

[0065] Yield strength YS: 1100MPa or more The steel sheet of this embodiment has a YS of 1100 MPa or more, preferably 1150 MPa or more, and more preferably 1200 MPa or more. The steel sheet of this embodiment preferably has a YS of 1470 MPa or less.

[0066] Yield ratio YR: 0.75 or more (optimal condition) The steel sheet of this embodiment preferably has a YR of 0.75 or more, more preferably 0.80 or more, and preferably has a YR of 1.0 or less, where YR=YS / TS.

[0067] In one embodiment of the present invention, a method for producing a steel sheet (high-strength steel sheet) includes preparing an unplated steel sheet having the above-mentioned composition, and annealing the steel sheet under predetermined conditions. Specifically, the annealing includes heating the steel sheet to a predetermined heating temperature T1, holding the steel sheet at T1 for a predetermined time t1, continuously cooling the steel sheet to a predetermined cooling stop temperature T2, holding the steel sheet at T2 for a predetermined time t2, heating the steel sheet to a predetermined tempering temperature T3, holding the steel sheet at T3 for a predetermined time t3, and then cooling the steel sheet to 50°C or less. This method allows the steel sheet having the above-mentioned composition, structure, and mechanical properties to be suitably produced.

[0068] In the present embodiment, the unplated steel sheet to be annealed is preferably a cold-rolled steel sheet. A suitable manufacturing process for the cold-rolled steel sheet will be described below.

[0069] First, a steel slab having the above-mentioned composition is manufactured. The manufacturing method of the steel slab is not particularly limited, and a known melting method using a converter, an electric furnace, etc. can be adopted. The steel slab is preferably manufactured by a continuous casting method in order to prevent macrosegregation.

[0070] The steel slab is then hot-rolled to obtain a hot-rolled steel sheet. Examples of methods for hot-rolling the steel slab include a method of rolling the steel slab after heating it, a method of directly rolling the steel slab after continuous casting without heating it, and a method of heating the steel slab for a short time after continuous casting and rolling it. The slab heating temperature, slab soaking time, finish rolling temperature, and coiling temperature in hot rolling are not particularly limited, but the slab heating temperature is preferably 1100°C or more and 1300°C or less, the slab soaking time is preferably 30 minutes or more and 250 minutes or less, the finish rolling temperature is preferably the Ar3 transformation point or more, and the coiling temperature is preferably 350°C or more and 650°C or less.

[0071] Next, the hot-rolled steel sheet is pickled. Pickling removes oxides from the steel sheet surface, which contributes to ensuring good phosphating properties and plating quality in the final high-strength steel sheet product. Pickling may be performed once or multiple times.

[0072] The hot-rolled steel sheet is then cold-rolled to obtain a cold-rolled steel sheet. The cold-rolling may be performed as is after pickling, or may be performed after heat treatment and then cold rolling. The reduction ratio in cold rolling is not particularly limited, but is preferably 30% or more and 80% or less. The number of rolling passes and the reduction ratio of each pass are not particularly limited, and the effects of the present invention can be obtained. The thickness of the cold-rolled steel sheet is not particularly limited, but is preferably 0.6 mm or more and 2.0 mm or less.

[0073] Heating temperature T1: 850℃ or more If the heating temperature T1 is less than 850°C, the annealing process will be performed in the two-phase region of ferrite and austenite, and the amount of ferrite will exceed 5% after annealing, making it difficult to achieve a TS of 1470 MPa or more. Therefore, the heating temperature T1 is set to 850°C or more (austenitization temperature region), and preferably 860°C or more. There is no particular upper limit to the heating temperature T1, but due to production technology constraints, the heating temperature T1 is preferably set to 1000°C or less.

[0074] Holding time t1 at heating temperature T1: 10 seconds or more and 1000 seconds or less If the holding time t1 is less than 10 seconds, austenitization is insufficient, the amount of ferrite after annealing exceeds 5%, and it becomes difficult to achieve a TS of 1470 MPa or more. Therefore, the holding time t1 is set to 10 seconds or more, preferably 50 seconds or more, and more preferably 100 seconds or more. On the other hand, if the holding time t1 exceeds 1000 seconds, the prior austenite grain size increases excessively, and the delayed fracture resistance property decreases. Therefore, the holding time t1 is set to 1000 seconds or less, preferably 500 seconds or less, and more preferably 400 seconds or less.

[0075] Average cooling rate θ1 from heating temperature T1 to 550℃: 16℃ / s or more If the average cooling rate θ1 is less than 16°C / s, bainite transformation occurs in the temperature range from heating temperature T1 to 550°C, the total amount of bainitic ferrite and fresh martensite becomes 9% or more, and the delayed fracture resistance property decreases. Therefore, the average cooling rate θ1 is set to 16°C / s or more, and preferably 20°C / s or more. There is no particular upper limit to the average cooling rate θ1, but due to constraints on production technology, the average cooling rate θ1 is preferably set to 300°C / s or less.

[0076] Average cooling rate θ2 from 550℃ to cooling stop temperature T2: 150℃ / s or less If the average cooling rate θ2 exceeds 150°C / s, carbon distribution from martensite to retained austenite during cooling is hindered, and the carbon concentration in the retained austenite becomes less than 0.35%, and as a result, the main cause of yielding of the steel sheet changes from tempered martensite to retained austenite, making it difficult to achieve a YS of 1100 MPa or more. Therefore, the average cooling rate θ2 is set to 150°C / s or less, preferably 120°C / s or less, and more preferably 100°C / s or less. There is no particular lower limit for the average cooling rate θ2, but due to constraints on production technology, the average cooling rate θ2 is preferably set to 5°C / s or more.

[0077] Continuous cooling from heating temperature T1 to cooling stop temperature T2 In one embodiment, it has been found that in order to realize a YS of 1100 MPa or more, it is necessary for the steel sheet to be continuously cooled from the heating temperature T1 to the cooling stop temperature T2, i.e., the steel sheet temperature is gradually decreased. For example, if an isothermal hold is performed for 1 second or more in the temperature range from the heating temperature T1 to the cooling stop temperature T2, it becomes difficult to realize a YS of 1100 MPa or more. Therefore, an isothermal hold is not performed for 1 second or more in the temperature range from the heating temperature T1 to the cooling stop temperature T2. Similarly, reheating is not performed in the temperature range from the heating temperature T1 to the cooling stop temperature T2.

[0078] Cooling stop temperature T2: 130℃ or more and 170℃ or less If the cooling stop temperature T2 exceeds 170°C, the amount of retained austenite exceeds 7%, and the delayed fracture resistance property is deteriorated. Therefore, the cooling stop temperature T2 is set to 170°C or less, and preferably 160°C or less. On the other hand, due to the constraints of production technology, the cooling stop temperature T2 is set to 130°C or more, and preferably 140°C or more.

[0079] Holding time at cooling stop temperature T2 t2: 1.0 seconds or more and 200.0 seconds or less If the holding time t2 is less than 1.0 seconds, the martensitic transformation is insufficient and the amount of retained austenite exceeds 7%, resulting in a decrease in delayed fracture resistance. Therefore, the holding time t2 is set to 1.0 seconds or more, and preferably 5.0 seconds or more. On the other hand, if the holding time t2 exceeds 200.0 seconds, the amount of carbide precipitation increases, so the carbon concentration in the retained austenite becomes less than 0.35%, and as a result, the main cause of the yield of the steel sheet changes from tempered martensite to retained austenite, making it difficult to achieve a YS of 1100 MPa or more. Therefore, the holding time t2 is set to 200.0 seconds or less, and preferably 150.0 seconds or less.

[0080] Average heating rate θ3 from cooling stop temperature T2 to tempering temperature T3: 10℃ / s or more If the average heating rate θ3 is less than 10°C / s, the amount of carbide precipitation increases, so the carbon concentration in the retained austenite becomes less than 0.35%, and as a result, the main cause of the yield of the steel sheet changes from tempered martensite to retained austenite, making it difficult to achieve a YS of 1100 MPa or more. Also, if the average heating rate θ3 is less than 10°C / s, bainite transformation occurs, the total amount of bainitic ferrite and fresh martensite becomes 9% or more, and the delayed fracture resistance property decreases. Therefore, the average heating rate θ3 is set to 10°C / s or more, preferably 15°C / s or more. There is no particular upper limit for the average heating rate θ3, but due to constraints on production technology, the average cooling rate θ3 is preferably set to 200°C / s or less.

[0081] Tempering temperature T3: 280℃ or higher and 350℃ or lower If the tempering temperature T3 exceeds 350°C, the tempering of martensite proceeds excessively, making it difficult to achieve a TS of 1470MPa or more. Therefore, the tempering temperature T3 is set to 350°C or less, preferably 340°C or less. On the other hand, if the tempering temperature T3 is less than 280°C, carbon distribution from martensite to austenite becomes insufficient, and the carbon concentration in the retained austenite becomes less than 0.35%, and as a result, the main cause of the yield of the steel sheet changes from tempered martensite to retained austenite, making it difficult to achieve a YS of 1100MPa or more. Therefore, the tempering temperature T3 is set to 280°C or more, preferably 290°C or more.

[0082] Holding time at tempering temperature T3: 10 seconds or more and 1000 seconds or less If the holding time t3 is less than 10 seconds, the bainite transformation at the tempering temperature T3 does not proceed, and the amount of retained austenite exceeds 7%, resulting in a decrease in delayed fracture resistance. Therefore, the holding time t3 is set to 10 seconds or more, preferably 50 seconds or more, and more preferably 100 seconds or more. On the other hand, if the holding time t3 exceeds 1000 seconds, the tempering of martensite proceeds excessively, making it difficult to achieve a TS of 1470 MPa or more. Therefore, the holding time t3 is set to 1000 seconds or less, preferably 800 seconds or less, and more preferably 600 seconds or less.

[0083] Cool the steel plate to below 50℃ After the steel sheet is held at the tempering temperature T3, the steel sheet is cooled to 50° C. or lower, preferably to about room temperature. The cooling method and conditions are not particularly limited.

[0084] In various embodiments, the steel sheet is then subjected to temper rolling at an elongation rate of 0.1% or more. As a result, the residual austenite with a low carbon concentration undergoes deformation-induced martensite transformation, increasing the carbon concentration in the residual austenite and improving the YS. Therefore, when temper rolling is performed, the elongation rate is preferably 0.1% or more. There is no particular upper limit to the elongation rate, but if the elongation rate is too high, the effect of improving the YS becomes saturated. In addition, from the viewpoint of constraints on manufacturing equipment, the elongation rate is preferably 1.0% or less. EXAMPLES

[0085] Steel having the composition shown in Table 1 (the balance being Fe and unavoidable impurities) was melted in a converter and formed into a slab by a continuous casting method.

[0086] [Table 1] TIFF0007657372000002.tif245125TIFF0007657372000003.tif245124

[0087] The obtained slab was then heated, hot-rolled, pickled, and cold-rolled to obtain a cold-rolled steel sheet. The cold-rolled steel sheet was then annealed under the conditions shown in Table 2, and then cooled to room temperature to obtain a high-strength steel sheet. In some comparative examples, the steel sheet was held at the intermediate holding temperature and for the intermediate holding time shown in Table 2 between the heating temperature T1 and the cooling stop temperature T2. In some invention examples, the steel sheet was cooled to room temperature, and then temper-rolled at the elongation rate shown in the "SKP" column in Table 2.

[0088] [Table 2] TIFF0007657372000005.tif245155TIFF0007657372000006.tif245155TIFF0007657372000007.tif245142

[0089] For each of the high-strength steel sheets obtained as described above, the volume fraction of tempered martensite, the volume fraction of retained austenite, the total volume fraction of bainitic ferrite and fresh martensite, the volume fraction of ferrite, and the carbon concentration in the retained austenite were determined according to the methods described above. The results are shown in Table 3.

[0090] [Table 3] TIFF0007657372000009.tif231170TIFF0007657372000010.tif232170TIFF0007657372000011.tif245165

[0091] Moreover, the high strength steel plate of each example was subjected to the following tensile test and evaluation of delayed fracture resistance.

[0092] [Tensile test] A JIS No. 5 test piece (gauge length 50 mm, parallel width 25 mm) was taken from each high-strength steel plate so that the longitudinal direction of the test piece was perpendicular to the rolling direction, and a tensile test was carried out according to JIS Z 2241. The crosshead speed was 1.67 × 10 -1 A tensile test was carried out under conditions of mm / s, and YS and TS were measured. In the present invention, a TS of 1470 MPa or more and 1650 MPa or less was judged to be acceptable. YS of less than 1100 MPa was rated as "x", that of 1100 MPa or more and less than 1200 MPa was rated as "○", and that of 1200 MPa or more was rated as "◎", and that of 1100 MPa or more was judged to be excellent. In addition, the yield ratio YS was calculated from YS and TS, and is shown in Table 3.

[0093] [Evaluation of delayed fracture resistance] The delayed fracture resistance was evaluated by an immersion test. The high-strength steel plate of each example was sheared to 30 mm x 110 mm with the longitudinal direction perpendicular to the rolling direction, and a hole for a bolt was drilled to prepare a test piece. The rake angle during shearing was standardized to 0°, and the shear clearance was changed to 5, 10, 15, 20, 25, 30, and 35%. After bending the test piece with a 90° V-bending punch and die with a tip curvature radius of 10 mm, a stress of 1000 MPa was applied to the apex of the test piece with a bolt. The test piece in the stressed state was immersed in hydrochloric acid at 25°C and pH 3 for 100 hours. The shear clearance range where no cracks occurred was evaluated as "x", the range where no cracks occurred was 10% or more but less than 15% was evaluated as "○", and the range where no cracks occurred was 15% or more was evaluated as "◎". A shear clearance range of 10% or more where cracks do not occur was determined to have excellent resistance to delayed fracture.

[0094] As is clear from Table 3, the examples of the present invention have a TS of 1470 MPa or more and 1650 MPa or less, a YS of 1100 MPa or more, and are excellent in delayed fracture resistance, whereas the comparative examples are inferior in at least one of TS, YS, and delayed fracture resistance. [Industrial Applicability]

[0095] The high-strength steel sheet of the present invention can be suitably used as a structural member for automobile parts and the like, and contributes to improving fuel efficiency by reducing the weight of the vehicle body.

Claims

1. In mass percent, C: 0.24-0.28%, Si: 0.40-0.80%, Mn: 2.30-2.70%, Cu: 0.010-1.000%, P: 0.001-0.100%, S: 0.0001-0.0200%, Al: 0.010 to 0.050%, and N: 0.0010-0.0100% Contains Optionally, Ti: 0.1000% or less, B: 0.01000% or less, Nb: 0.1000% or less, Cr: 1.00% or less, V: 0.100% or less, Mo: 0.500% or less, Ni: 0.500% or less, As: 0.500% or less, Sb: 0.200% or less, Sn: 0.200% or less, Ta: 0.100% or less, Ca: 0.0200% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co: 0.0200% or less, Zr: 0.0200% or less, and REM: 0.0200% or less and a component composition further comprising one or more selected from the group consisting of: In terms of volume ratio, Tempered martensite: 90% or more, Retained austenite: 1 to 7% Bainitic ferrite and / or fresh martensite: 3 to 9% in total; and Ferrite: 0-5% a structure in which the carbon concentration in the retained austenite is 0.35% or more; A tensile strength TS of 1470 to 1650 MPa; A yield strength YS of 1100 MPa or more; A steel plate having

2. The steel plate according to claim 1, wherein the yield strength YS is 1200 MPa or more.

3. An unplated steel sheet having the composition according to claim 1 is prepared, The steel plate is heated to a heating temperature T1 of 850° C. or higher, The steel sheet is held at the heating temperature T1 for 10 to 1000 seconds, The steel sheet is cooled from the heating temperature T1 to a cooling stop temperature T2 of 130 to 170 ° C. (i) an average cooling rate from the heating temperature T1 to 550° C.: 16° ​​C. / s or more; and (ii) Average cooling rate from 550° C. to the cooling stop temperature T2: 150° C. / s or less Continuously cool under the conditions of The steel sheet is held at the cooling stop temperature T2 for 1.0 to 200.0 seconds, The steel plate is heated from the cooling stop temperature T2 to a tempering temperature T3 of 280 to 350 ° C. at an average heating rate of 10 ° C. / s or more, The steel plate is held at the tempering temperature T3 for 10 to 1000 seconds; The steel plate is cooled to 50° C. or less. A method for producing a steel plate, comprising the steps of: producing the steel plate according to claim 1 .

4. The method for producing a steel sheet according to claim 3, further comprising a step of subjecting the steel sheet to temper rolling at an elongation rate of 0.1 to 1.0% after the cooling to 50°C or less.

Citation Information

Patent Citations

  • JPP6729835B

  • High-strength cold-rolled steel sheet

    US20190040490A1

  • Steel sheet and manufacturing method therefor

    US20200157647A1

  • High-strength cold-rolled steel sheet

    WO2017141953A1

  • Steel plate and production method therefor

    WO2018190416A1